Brains at Brand Touchpoints: A Consumer Neuroscience Study of Information Processing of Brand Advertisements and the Store Environment in Compulsive Buying - Dalia Bagdziunaite (Copenhagen Business School (CBS), 2018)
Background. Compulsive buying—defined as excessive, uncontrolled, and repetitive buying— is a serious problem in today's society, driven by consumeristic values and reinforced by marketing efforts. However, the research on the external influences (e.g., brand information) and underlying processes that explain consumer behavior in brand-manifesting situations in compulsive buying is relatively scarce. This thesis provides an integrative literature review and two experimental studies that yield cross-disciplinary insights into the compulsive buying phenomenon. The thesis aims to study the cognitive, emotional, and behavioral responses that characterize consumer-brand interactions at relevant brand touchpoints in compulsive buying. Research methodology. Two experimental studies investigate similarities and differences between two groups of consumers with high and low compulsive buying tendencies (CBTs) at two brand touchpoints that represent a pre-purchase and purchase phase of the consumer journey. Multimodal consumer neuroscience tools (i.e., eye-tracker, EEG, and EDA) are employed to collect neurophysiological and physiological responses during exposure to marketing information. The first study examines consumer information processing of advertisements during a simulated TV commercial-viewing experiment. The second study investigates consumer information processing of store environments during a field experiment conducted in two single-brand fashion-apparel stores (i.e., low-end vs. high-end). Findings. The findings from the first study indicate that, regardless of their CBT level, consumers tend to allocate a relatively equal amount of cognitive resources to attend to, process, and remember exposed advertising information during the entire duration of commercial viewing. The two groups differed in their visual processing of brand elements only when viewing advertisements related to social cause. In the consumer group with a high CBT, a higher cognitive workload was linked to a lower probability of subsequent brand recognition. The findings from the second study revealed that, regardless of the fashion-store type, consumers with a high CBT chose items that were more expensive than consumers with a low CBT. The changes in physiological arousal during the first minute of shopping showed that, although both consumer groups were more emotionally responsive to the high-end than the low-end fashion store, the emotional receptivity in both groups was expressed in different physiological responses. Specifically, consumers with a high CBT demonstrated a higher frequency and a shorter duration of emotional responses, whereas consumers with a low CBT showed a higher amplitude of emotional responses in the high-end fashion store than in the low-end fashion store. The results indicate that there are two potentially different mechanisms that occur in the two consumer groups during encounters with store information. Conclusions. This thesis provides theoretical, methodological, managerial, and societal contributions. This research highlights the fact that compulsive buying is a complex phenomenon and that researchers should address both internal and external influences, examine the unconscious processes and mechanisms, and study consumer responses to marketing information in more naturalistic settings. The thesis also promotes the integration of consumer neuroscience tools with the compulsive buying research practice, aims to increase the awareness of the problem of compulsive buying, and encourages the development of novel, technologybased and scientifically driven consumer-behavior-monitoring policies.
hdl:10398/9643
Keywords: 650